FONDART as a Funding Source for Community Archives in Chile (GESTIÓN Y TENDENCIAS, 2024)
This exploratory study examines the sustainability of community archives in Chile funded by the National Fund for Cultural and Arts Development (FONDART) between 2012 and 2022. The authors stress that community archives are essential for preserving collective memory and local identities, which official history often renders invisible. The research nevertheless reveals a structural problem: dependence on competitive, short-term grant funding jeopardizes the continuity of these projects.Analysis of the FONDART guidelines reveals restrictive changes over the past decade, such as the reduction of maximum awards (from CLP 30 million to CLP 15 million) and the shortening of implementation periods from 24 to 12 months. Of the 45 community archive projects identified over the period, most were found unable to remain active once state funding ceased. This is attributed to the limited technical capacity of the teams (usually volunteers), the absence of long-term management models, and the precariousness of digital infrastructure, where many websites cease to exist or to be updated once the project ends. The article concludes that public policy must be rethought in order to guarantee not only the creation but the sustainability of these repositories of memory.
Keywords: community archives; collective memory; FONDART; cultural sustainability; digital heritage